(untitled) (Indian Journal of Public Health Research & Development, 2026)
Mental health care in India continues to be shaped largely by a biomedical paradigm that prioritises diagnosis and pharmacological treatment while insufficiently addressing the social and structural determinants of psychological distress. Such an approach risks pathologising normal responses to chronic adversity and inadequately serving populations facing poverty, gender-based violence, caste discrimination and other forms of structural oppression. This commentary argues for a shift towards inclusive, community-based mental health systems integrated within primary health care. Drawing on evidence from Indian programmes such as the National Mental Health Programme, District Mental Health Programme, VISHRAM and Sangath, the paper highlights the need for culturally responsive, decentralised and socially grounded approaches that move beyond pharmacological reductionism to improve population mental wellbeing.